The Working Group on Drugs and Pharmaceuticals for the Tenth Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 2002)
The planning Commission has constituted a working Group on Drugs and Pharmaceuticals for the Tenth Five Year Plan Vide order No.I&M-3(25)/2000 dated 14th December, 2000. The constitution and the terms of reference of the Working Group are given at Annexure-1. The Working Group deliberated on the general issues concerning the Pharmaceutical Industry in its first meeting held on 20th April 2001 and decided to constitute three Sub-Groups to give their reports on specific matters as follows: (a)The Sub-Group I was on the Status and Structure of the Pharmaceutical Industry covering terms of reference nos.1,2,8,12&13. (b)Sub-Group II was on present Regulatory mechanism covering terms of reference nos.3,9,10,11 & 13. (c)The Sub- Group-III was on R&D training & development infrastructure, employment generation etc. covering terms of reference Nos. 4, 5, 6 & 7.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Tenth Five Year Plan- The Working Group on Drugs and Pharmaceuticals; Pharmacognosy